Challenges of SARS-CoV-2 and conflicting PPE guidelines. (2nd November 2020) - Master, Shamima; Gerrard, Mark
Abstract : During the coronavirus disease 2019 (COVID-19) pandemic, personal protective equipment (PPE) has become a contentious issue in healthcare settings, no more so than in the prehospital environment. The current severe acute respiratory syndrome 2 virus (SARS-CoV-2) has pathogenic and transmission similarities to previous coronaviruses, severe acute respiratory syndrome (SARS-CoV) and Middle Eastern respiratory syndrome (MERS-CoV). There are differences in global and domestic PPE guidelines concerning SARS-CoV-2.